Duck enteritis virus UL54 is an IE protein primarily located in the nucleus - Liu, Chaoyue (Virol J, 2015)
BACKGROUND: The UL54 protein of Duck Enteritis Virus (DEV) is a homolog of herpes simplex virus-1 (HSV-1) immediate-early infectious cell protein 27 (ICP27), a multifunctional protein essential for viral infection. Nonetheless, there is little information on the UL54 protein of DEV. METHODS: The UL54 gene was cloned into the pPAL7 vector, and the recombinant protein, expressed in the E. coli Rosetta, was used to produce a specific antibody. Using this antibody, Western blotting and indirect immunofluorescence analysis (IFA) were used to analyze the expression level and intracellular localization, respectively, of UL54 in DEV-infected cells at different times. Real-time quantitative reverse transcription PCR (RT-PCR) and the pharmacological inhibition test were utilized to ascertain the kinetic class of the UL54 gene. RESULTS: UL54 was expressed as a fusion protein of approximately 66.0 kDa using the prokaryotic expression system, and this protein was used to generate the specific anti-UL54 antibody. The UL54 protein was initially diffusely distributed throughout the cytoplasmic region; then, after 2 h, it gradually distributed into the nucleus, peaking at 24 h, and complete localization to the nucleus was observed thereafter. The UL54 transcript was detected as early as 0.5 h, and peak expression was observed at 24 h. The UL54 gene was insensitive to the DNA polymerase inhibitor Ganciclovir (GCV) and the protein synthesis inhibitor Cycloheximide (CHX), both of which confirmed that UL54 was an immediate early gene. CONCLUSIONS: The DEV UL54 gene was expressed in a prokaryotic expression system and characterized for expression level, intracellular localization and gene kinetic class. We propose that these results will provide the foundation for further functional analyses of this gene.